Charting the Future: Credentialing, Privileging, Quality, and Evaluation in Clinical Ethics Consultation - Dubler, Nancy Neveloff (The Hastings Center report, 2009)
Clinical ethics consultation has become an important resource, but unlike other health care disciplines, it has no accreditation or accepted curriculum for training programs, no standards for practice, and no way to measure effectiveness. The Clinical Ethics Credentialing Project was launched to pilot-test approaches to train, credential, privilege, and evaluate consultants.